Applying technology acceptance model to investigate the use of smartphone advertising in Malaysia - Jan, Muhammad Tahir; Jager, Johan W de; Ameziane, Alileche Mohamed; Sultan, Naheed (AMH International, 2019)
The rapid development of internet, mobile information technologies and communications keep offering unprecedented concepts in the way people use new technology and communicate information. This also applies to Malaysia where this study was performed. The main objective of this paper is to investigate which factors affect the use of smartphone advertising most. For this purpose, four main services providers, namely, U-mobile, Maxis, DiGi and Celcom, were selected for data collection. A self-administered questionnaire was distributed through a convenience sampling to 400 smartphone users in a pre-defined area of Malaysia. Three hundred and forty usable questionnaires were used for the purpose of the data analysis. First, descriptive analysis is undertaken followed by a reliability test and exploratory factor analysis. Second, a two-step structural equation modelling approach is adopted where confirmatory factor analysis (CFA) was conducted followed by hypotheses testing. The results indicate that perceived usefulness has a stronger impact on attitude towards smartphone advertising followed by subjective knowledge. Furthermore, attitude towards smartphone advertising also resulted in a significant influence on the use of smartphone advertising. The findings of this study not only contribute to the knowledge but could also assist policymakers with informed decisions about market penetration.